Understanding the potential key risk factors associated with teen driver crashes in the United States: a literature review - Md Mahmud Hossain; M. Ashifur Rahman (Digital Transportation and Safety)
This article is a compilation of teen driver crash contributing factors typically extractable from the crash data collection system in the United States. Tremendous research effort has been undertaken over the decades to comprehend teen driver crash risks, as teen drivers continue to be over-involved in crashes even when accounting for the driving exposure. This article presents the contexts of crash factors related to operating conditions, roadway, vehicle, and driver and their unique influences on teen driver crashes in terms of estimated risk, prevalence, and estimated likelihood mainly from descriptive and analytical studies. The key variables are selected based on the number of studies that considered each risk factor for analysis. The understanding of crash factors could be translated into graduated driver licensing and other teen driver safety programs. While the discussions were grounded in crash studies carried out in the United States, the insights gleaned from these studies hold the potential to offer valuable guidance to other countries. For example, the insights and discussions can serve as a catalyst for the development and improvement of driver education programs tailored to address the specific requirements and difficulties confronted by their teenage drivers.